Considerations on Ergonomic Issues in Physiotherapy Activity - Darabont Vlad Andrei (MATEC Web of Conferences, 2021)
Nowadays, the ergonomic issues become more and more important in all economic activity domains. Work-related Musculoskeletal Disorders (MSDs) represent the main problem generated by the poor ergonomic design of the workplaces. The healthcare domain involves high level ergonomic risks related to physical and mental load of the work which could lead to MSDs. The paper presents an analysis of these ergonomic risks for physiotherapy activity and identifies potential measures to improve the health and safety in this domain. The physical load of the physiotherapist’s work is generated by the risk factors such as awkward postures, repetitive movement or working with patients with motor disabilities. The mental load of the physiotherapist’s work depends on risk factors such as working with patients with cognitive impairment and daily or weekly patient flows. The proposed preventive measures are organisational and technical. The organisational measures are based on the requirements of the occupational health and safety (OHS) legislation and on the good practice examples. The technical measures are based on the analysing the documentation of physiotherapy modern equipment. The results of the study can be used to improve the ergonomics and the health and safety of any workplace in physiotherapy activity.